2019
DOI: 10.3390/ijms20030622
|View full text |Cite
|
Sign up to set email alerts
|

Novel Zebrafish Mono-α2,8-sialyltransferase (ST8Sia VIII): An Evolutionary Perspective of α2,8-Sialylation

Abstract: The mammalian mono-α2,8-sialyltransferase ST8Sia VI has been shown to catalyze the transfer of a unique sialic acid residues onto core 1 O-glycans leading to the formation of di-sialylated O-glycosylproteins and to a lesser extent to diSia motifs onto glycolipids like GD1a. Previous studies also reported the identification of an orthologue of the ST8SIA6 gene in the zebrafish genome. Trying to get insights into the biosynthesis and function of the oligo-sialylated glycoproteins during zebrafish development, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 78 publications
(135 reference statements)
2
13
0
Order By: Relevance
“…The orthologues of ST8Sia I and ST8Sia V involved in gangliosides biosynthesis are identified in all the investigated genomes, suggesting a high conservation of the gangliosides biosynthetic pathways in vertebrates (Supplemental Table S1). Similarly, the ST8Sia III and the recently described fish ST8Sia VIII [17] could be found in all the Actinopterygii (ray-finned fishes) genomes ( Figure 1; Supplemental Table S1). Intriguingly, multiple copies of st8sia-related gene sequences were identified in Teleost genomes and their number varied considerably from one fish order or species to another.…”
Section: In Silico Identification and Phylogenetic Reconstruction Of supporting
confidence: 52%
See 2 more Smart Citations
“…The orthologues of ST8Sia I and ST8Sia V involved in gangliosides biosynthesis are identified in all the investigated genomes, suggesting a high conservation of the gangliosides biosynthetic pathways in vertebrates (Supplemental Table S1). Similarly, the ST8Sia III and the recently described fish ST8Sia VIII [17] could be found in all the Actinopterygii (ray-finned fishes) genomes ( Figure 1; Supplemental Table S1). Intriguingly, multiple copies of st8sia-related gene sequences were identified in Teleost genomes and their number varied considerably from one fish order or species to another.…”
Section: In Silico Identification and Phylogenetic Reconstruction Of supporting
confidence: 52%
“…Interestingly, our recent studies pointed to the fact that the st8sia gene family appears to be much larger in teleost fish genomes [14,17]. The emergence of several novel vertebrate mono-α2,8-sialyltransferases subfamilies like ST8Sia VII and ST8Sia VIII was described in this first group of ST8Sia and their enzymatic specificities remain to be determined.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To first validate that the Cy5-tagged CMP-Sia analog can be incorporated by sialyltransferases in live cells, we examined the feasibility of transferring Sia-sulfo-Cy5 onto the cell-surface of sialylation-defect Chinese Hamster Ovary (CHO) mutant Lec2, using three recombinant human STs (hST3Gal1, hST3Gal4, hST6Gal1). 21 ST6Gal1/2 and ST3Gal 1/2/3/4/5 are evolutionarily conserved in human and zebrafish genomes and STs in both species share high homology, [22][23][24] therefore it is reasonable to use the human homologs to examine the donor substrate scope. After incubation with STs and probe A, we detected intense Cy5 fluorescence on Lec2 cells, but not in the cells treated without STs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we observed that in the head region, fucosylatd glycans have a quicker turnover rate than sialylated glycans. 24,36,37 Studies by Stanley, Haltiwanger, and Taniguchi have shown that knockout of FUT8, POFUT1 or POFUT2 is lethal to mice. [38][39][40][41] In addition, congenital mutations of the Golgi localized GDP-fucose transporter SLC35C1 cause leukocyte adhesion deficiency type II, whose manifestation is severe developmental and immune deficiencies.…”
Section: Discussionmentioning
confidence: 99%